A practical framework for remediating unprofessional behavior and for developing professionalism competencies and a professional identity. (4th March 2019) - Barnhoorn, Pieter C.; Houtlosser, Mirjam; Ottenhoff-de Jonge, Marleen W.; Essers, Geurt T. J. M.; Numans, Mattijs E.; Kramer, Anneke W. M.
Abstract: The relatively new term "Professional Identity Formation" (PIF) complements behavior-based and attitude-based perspectives on professionalism. Unprofessional behavior and its remediation should also be addressed from this perspective. However, a framework is needed to guide discussion and remediation of unprofessional behavior, which can encompass behavior-based, attitude-based, and identity-based perspectives on professionalism. To this end, the authors propose a multi-level professionalism framework which describes, apart from professional behavior, more levels which influence professional performance: environment, competencies, beliefs, values, identity, and mission. The different levels can provide tools for educators to address and discuss unprofessional behavior with their students in a comprehensive way. By reflecting on all the different levels of the framework, educators guard themselves against narrowing the discussion to either professional behavior or professional identity. The multi-level professionalism framework can help educators and students to gain a better understanding of the root of unprofessional behavior, and of remediation strategies that would be appropriate. For despite the recent emphasis on PIF, unprofessional behavior and its remediation will remain important issues in medical education.